2017
DOI: 10.1002/dys.1571
|View full text |Cite
|
Sign up to set email alerts
|

What can Parents' Self‐report of Reading Difficulties Tell Us about Their Children's Emergent Literacy at School Entry?

Abstract: Research has linked family risk (FR) of reading difficulties (RD) with children's difficulties in emergent literacy development. This study is the first to apply parents' self‐report of RD as a proxy for FR in a large sample (n = 1171) in order to test group differences in children's emergent literacy. Emergent literacy, the home literacy environment and children's interest in literacy and letters were compared across different groups of FR children around the school entry. The FR children performed lower in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(48 citation statements)
references
References 45 publications
(83 reference statements)
5
41
2
Order By: Relevance
“…A possible explanation for these inconsistent findings regarding associations between FR and the HLE is parental level of education and/or socioeconomic background (Esmaeeli et al, 2018;Hamilton et al, 2016). In the studies in which the HLE did not differ between FR and Not-FR groups, there were no differences between FR and Not-FR groups in parental education (Torppa et al, 2007) or maternal education (Elbro et al, 1998).…”
Section: Environmental Protective Factors Family Risk and Children'mentioning
confidence: 96%
See 3 more Smart Citations
“…A possible explanation for these inconsistent findings regarding associations between FR and the HLE is parental level of education and/or socioeconomic background (Esmaeeli et al, 2018;Hamilton et al, 2016). In the studies in which the HLE did not differ between FR and Not-FR groups, there were no differences between FR and Not-FR groups in parental education (Torppa et al, 2007) or maternal education (Elbro et al, 1998).…”
Section: Environmental Protective Factors Family Risk and Children'mentioning
confidence: 96%
“…The association between FR and the HLE is less clear and data are limited (Snowling & Melby-Lervåg, 2016). Some studies report no differences in HLE between FR families and Not-FR families (Elbro et al, 1998;Torppa et al, 2007), whereas others studies report a relatively disadvantageous HLE for FR children compared with Not-FR children (Dilnot et al, 2017;Esmaeeli, Lundetrae, & Kyle, 2018;Hamilton et al, 2016). Dilnot et al (2017) found that FR children experienced more environmental adversities than Not-FR children.…”
Section: Environmental Protective Factors Family Risk and Children'mentioning
confidence: 99%
See 2 more Smart Citations
“…Familial risk was deemed to be present where parents had reported the existence of at least one close relative (mother, father or sibling) with RD. This self-report measure has previously proven to be a valid and reliable way of collecting information about parents' RD (Esmaeeli et al, 2018). Parents of 20.1 per cent of the students in the Norwegian sample reported that their child's mother, father or both had experienced RD.…”
Section: Familial Risk Of Reading Difficulties (Rd)mentioning
confidence: 99%